Penerapan Pendekatan Analisis Transaksional dalam kelompok Berbasis Kato Nan Ampek - Zulhelmi Narti; Yeni Karneli; Netrawati Netrawati (Jurnal Counseling Care, 2022)
Free association makes humans insensitive to cultural norms that exist in society, as well as the ethics of communicating with others (interpersonal communication). In Minangkabau, communication with other people has rules and ethics called kato nan ampek. When individuals do not understand and do not apply kato nan ampek in communication, it is called Minang Indak Tau di Nan Ampek. Kato Nan Ampek communication model in Minangkabau culture as an effective pattern of communication to build counselor and counselee relationships. The purpose of this research is to improve the counselee's interpersonal communication related to kato nan ampek. This study uses the library research research method. Data analysis technique using content analysis. The results of the study show that communication patterns greatly determine the success of counseling. Kato Nan Ampek's communication model can be an alternative in implementing counseling services. The counselee's interpersonal communication skills can be improved for the better through group counseling with a transactional analysis approach (AT).Keywords: interpersonal communication, kato nan ampek, counseling transactional